ANALISIS PERILAKU DINAMIK SISTEM POROS-ROTOR 3D - Asmara Yanto; Rachmat Hidaya (Jurnal Teknik Mesin, 2014)
In the system of rotating shaft-rotor, vibration problems often occur. Therefore, in order vibration spectrum analysis can be performed with good and safe operating speed limits can be determined properly, then the information on the natural frequency and critical speed of shaft-rotor system must be known well too. Natural frequency of the rotor-shaft system depends on the speed of rotation. In this study we analyzed the dynamic behavior of a shaft-rotor system model by using 3D finite element method and direct method. The analysis was performed to obtain the critical rotation rates and visualizing mode shapes of the shaft-rotor system model 3D. Here, shaft-rotor system model consists of a 3D multi-storey shaft which is divided into 48 elements, two rivet shaft bearings, two disks, each of which is divided into 12 elements. Shaft speed in RPM varied from 0 to 24000 RPM with 100 RPM intervals. For each rotation axis arranged mass matrix, damping matrix, and stiffness matrix systems using the finite element method. The price of natural frequency and mode shape vector price is determined by using the direct method. From the analysis that has been done, the natural frequency obtained 96 forward and 96 backward natural frequency. For 2 pieces of personal frequencies forward and 2 backward the first natural frequency obtained 7 pieces of critical shaft rotation rates. From the visualization mode shape for the first 4 rounds of the critical mode shape obtained at the first natural frequency is equal to the forward mode shape at the first natural frequency and the backward mode shape at the second natural frequency is equal to the forward mode shape at the second natural frequency backward. From the visualization mode shape for 3 rounds last critical mode shape obtained in 2 pieces forward of the first natural frequency and mode shape on the same 2 pieces of the first natural frequency equal backward.